2015
DOI: 10.1002/cjoc.201500283
|View full text |Cite
|
Sign up to set email alerts
|

Multiple‐Stimuli Responsive Luminescent Gels Based on Cholesterol Containing Benzothiadiazole Fluorophores

Abstract: Two new fluorescent organogelators based on cholesterol containing benzothiadiazole group have been designed and synthesized. Three methods for gels preparation have been presented, such as heating-cooling process, ultrasonic treatment and mixed solvents under room temperature. For both of the gels, their states and emission colors exhibit striking changes upon addition of Hg 2+ . The gelation properties, structural characteristics and fluorescence of the gels were studied by FT-IR, UV-Vis absorption and PL sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Stimuli-responsive fluorescent materials have gained much exposure in recent years due to their potential applications as sensors, bioimaging, memory media, and displays. Chemical substances, , temperature, light, pH, electricity, and mechanical force are the typical stimuli utilized to change the fluorescent behaviors of these materials. To explore the mechanism of fluorescent switching and impart more functionality, many multiple stimuli-responsive fluorescent materials have been reported. For example, Huang et al have designed and synthesized two kinds of multiple stimuli-responsive fluorescent gels based on cholesterol-containing benzothiazole fluorophore, which is sensitive to temperature, solvent, ultrasound, and mercury ions. Yan et al have reported a mechanical-induced and solvent stimuli-responsive fluorescent change by assembling niflumic acid into the interlayer region of Zn–Al layered double hydroxides.…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli-responsive fluorescent materials have gained much exposure in recent years due to their potential applications as sensors, bioimaging, memory media, and displays. Chemical substances, , temperature, light, pH, electricity, and mechanical force are the typical stimuli utilized to change the fluorescent behaviors of these materials. To explore the mechanism of fluorescent switching and impart more functionality, many multiple stimuli-responsive fluorescent materials have been reported. For example, Huang et al have designed and synthesized two kinds of multiple stimuli-responsive fluorescent gels based on cholesterol-containing benzothiazole fluorophore, which is sensitive to temperature, solvent, ultrasound, and mercury ions. Yan et al have reported a mechanical-induced and solvent stimuli-responsive fluorescent change by assembling niflumic acid into the interlayer region of Zn–Al layered double hydroxides.…”
Section: Introductionmentioning
confidence: 99%